2009
DOI: 10.31671/dogus.2019.191
|View full text |Cite
|
Sign up to set email alerts
|

İMKB de Spekülatif Şişkinlerin Test Edilmesi

Abstract: Bu çalışmanın amacı İMKB'de spekülatif şişkinliklerin varlığının süre verisi (duration) modeli ile test edilmesidir. Bu amaçla İMKB'deki hisse senedi fiyatlarında süre bağımlılığı olup olmadığı McQueen ve Thorley (1994)'nin yaklaşımı kullanılarak farklı sektörler bazında araştırılmaktadır. Verilerin başlangıç tarihi IMKB 100

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The first study investigating the presence of financial balloons in stock exchange markets is the one carried out by Diba and Grossman in year 1985 and, since then, many other researchers examined the presence of balloons in stock exchange markets. Among the researchers, Brooks and Katsaris (2003), Altay (2008), Jiang et al (2010), Asako and Liu (2013), Anderson and Brooks (2014), Rotermann and Wilfling (2014), Baldi et al (2016), Tran (2017), Çağlı and Mandacı (2017), Anavatan and Kayacan (2018), He et al (2018), Akkaya (2018), Nartea et al (2018), Çıtak (2019), and Kılıç (2020) detected the financial balloons in stock exchange markets, Dezhbakhsh and Demirgüç-Kunt (1990), Chan et al (1998), Taşçı and Okuyan (2009), Yu and Hassan (2010), Yanık and Aytürk (2011), and Bozoklu and Zeren (2013) reported that there were no financial balloons in stock exchange markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first study investigating the presence of financial balloons in stock exchange markets is the one carried out by Diba and Grossman in year 1985 and, since then, many other researchers examined the presence of balloons in stock exchange markets. Among the researchers, Brooks and Katsaris (2003), Altay (2008), Jiang et al (2010), Asako and Liu (2013), Anderson and Brooks (2014), Rotermann and Wilfling (2014), Baldi et al (2016), Tran (2017), Çağlı and Mandacı (2017), Anavatan and Kayacan (2018), He et al (2018), Akkaya (2018), Nartea et al (2018), Çıtak (2019), and Kılıç (2020) detected the financial balloons in stock exchange markets, Dezhbakhsh and Demirgüç-Kunt (1990), Chan et al (1998), Taşçı and Okuyan (2009), Yu and Hassan (2010), Yanık and Aytürk (2011), and Bozoklu and Zeren (2013) reported that there were no financial balloons in stock exchange markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are various studies to test the existence of bubbles in the Turkish stock market with the help of employing different econometric methods. For example, Tasci and Okuyan (2009), Yu and Hasan (2010), and Yanık and Ayturk (2011) employ duration tests, while Ogut et al (2009) uses Artificial and Neural Networks and Support Machine. Parvar and Waters (2010) and Bozoklu and Zeren (2013) examine cointegration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the uses of different methologies, these studies yield mixed findings. In the existing literature, some studies suggest that there are speculative price (Taşçı and Okuyan, 2009;Yu and Hassan, 2010;Yanık ve Aytürk, 2011;Chang et al, 2016;Liaqat et al, 2018;), while others find no such correlation (Korkmaz et al, 2016;Koy, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%